KEPRIBADIAN GANDA TOKOH UTAMA DALAM DRAMA KOREA GODâS QUIZ (ì ì í´ì¦) : KAJIAN TEORI NEUROSIS HORNEY - , GALUH PAWESTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The theme of this research was literature psychology in which multiple personality as the focus on study. The subject of the study is a character of Godâs Quiz Korean Drama, Han Jin Woo who has two predominant personalities. The aim of this study is to find out the characters of Han Ji woo and the factors of those multiple personality disorder. Karen Horneyâs Neurosis Theory is used to analyze this multiple personality disorder. The data of this research is the conversation between characters which related with the theory. The data were observed and then analyzed by using personality psychological method. Based on Neurosis theory analysis, there are two characters of Han Ji Woo which are moving towards people and moving against people. Meanwhile, the third type in neurosis theory is not correlated with Han Jin Wooâs multiple personality. Things that caused Han Jin Woo have multiple personalities are psychological matters and physical matters. The first predominant character of Han Jin Woo is moving towards people type. This type has a tendency to grant others interest first than his own willing. This kind of personality are esteeming love very much. Han Jin Woo willingly to sacrify himself for the sake of Detective Kangâs life. On the other hand, the second predominant character of Han Jin Woo is moving against people in which shows his tendency to act aggressive and selfish . Han Jin Wooâs second personality is always prioritized his own ambition to be the best. He clearly hates others who able to surpass him. Things that caused Han Jin Woo have multiple personalities are psychological matters and physical matters. Psychological matters are a huge effect on Han Jin Woo mentality state. Physical matters are triggering the second Han Ji Woo come out. Keywords: multiple personality disorder, protagonist, drama, neurosis